2006
DOI: 10.1257/jep.20.3.47
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment Insurance: Strengthening the Relationship between Theory and Policy

Abstract: Ever since the U.S. federal-state system of unemployment insurance was founded in the 1930s, it has provided partial, temporary replacement of wages to eligible workers who lose jobs -- through no fault of their own -- (as determined by state-level regulations). Unemployment insurance is one of the largest social insurance programs in the United States, with benefits paid totaling about $34 billion in 2004. Economic theory can help us understand the challenges this complex program is likely to face over the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…Another simplifying assumption we made here, namely that the probability of a worker getting a job offer in any period t was equal to the firms' labor demand n t < 1, and thus independent of the worker's past employment status, should be relaxed as it neglects important channels generating unemployment persistence, such as for instance job search. Relaxing such an assumption would allow one particular possible negative consequence of raising unemployment insurance that we abstracted from to be taken into account; namely, that increased unemployment compensation might lower the intensity of job search and thus hurt employment (Baily 1978; Nicholson and Needels 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Another simplifying assumption we made here, namely that the probability of a worker getting a job offer in any period t was equal to the firms' labor demand n t < 1, and thus independent of the worker's past employment status, should be relaxed as it neglects important channels generating unemployment persistence, such as for instance job search. Relaxing such an assumption would allow one particular possible negative consequence of raising unemployment insurance that we abstracted from to be taken into account; namely, that increased unemployment compensation might lower the intensity of job search and thus hurt employment (Baily 1978; Nicholson and Needels 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that unemployment duration increases with unemployment benefits (Nicholson and Needels, 2006). Note, however, that rapid end of an unemployment spell can be considered only one positive outcome; others are also relevant, including good job match.…”
Section: Occupational Functioningmentioning
confidence: 93%
“…However, in recent years the triggers based on insured unemployment have rarely activated EB when total unemployment rises (Nicholson and Needels 2006). Under the original 1970 law, EB could be activated by a national trigger affecting all states, or a state-level trigger affecting EB only in that 14 The IUR is the rate of insured unemployed persons in a period as a percentage of the UI-covered employed persons in the period.…”
Section: Areas Of Explicit Federal-state Cooperation Permanent Federamentioning
confidence: 99%